Ketahanan Pangan Masyarakat Adat Sebagai Wujud Pemenuhan Ham Dalam Masa Pandemi Covid-19 - Josina Augustina Yvonne Wattimena; Vondaal Vidya Hattu (Faculty of Law, Universitas Pattimura, 2021)
This study aims to analyze and determine the food security of indigenous peoples during the Covid 19 pandemic and the legal implications of food security for indigenous peoples that were not fulfilled during the Covid 19 pandemic. This type of juridical normative research uses literature review based on theory, doctrine and norms laws relating to the issues discussed. This research is an explanatory analytical prescriptive by explaining the problems raised based on legal provisions, norms and theories and then analyzed qualitatively. In the end, we will draw a conclusion as an answer to the problems discussed. Based on the results of research on food security, indigenous peoples have been greatly affected by the COVID-19 pandemic. Moreover, the lands and territories of indigenous peoples have been under the control of companies exploiting their natural resources. Of course this will further exacerbate their rights to food needs. In international and national legal instruments, the State's responsibility to protect and fulfill their right to food has been formulated. The solutions to the various situations and conditions that hinder the implementation of State responsibility must be resolved. If the State does not immediately carry out its responsibilities related to basic rights such as the right to food, then the State will be deemed to have committed a violation and according to international law can be prosecuted.